Loneliness as a Biographical Disruption—Theoretical Implications for Understanding Changes in Loneliness - Morgan, Deborah J (J Gerontol B Psychol Sci Soc Sci, 2020)
OBJECTIVES: While a great deal is known about the risk factors that increase vulnerability to loneliness in later life, little research has explored stability and change in levels of loneliness. METHODS: Narrative interviews were conducted with 11 participants who were identified as being lonely during Wave 1 of the Maintaining Function and Well-being in Later Life Study Wales (CFAS Wales). The interviews were used to explore stability and change in levels of loneliness from the perspective of older people themselves. The interviews focused on participant’s perspectives of the events that triggered loneliness, stability, and change in levels of loneliness over time as well as participant’s responses to loneliness. RESULTS: The findings show that participants experienced losses and loneliness as biographical disruption. How participants and their wider social network responded to these losses had implications for the individual’s trajectory through loneliness. DISCUSSION: Drawing on a biographical lens, the study reframed the events that triggered loneliness as disruptive events. This article discusses the utility of biographical disruption in understanding stability and change in loneliness. The findings suggest how drawing on valued identities may help lonely adults transition out of loneliness.